Mapping the Chicxulub Impact Stratigraphy and Peak Ring Using Drilling and Seismic Data. Issue 8 (12th August 2021) - Christeson, G. L.; Morgan, J. V.; Gulick, S. P. S.
Abstract: We integrate high‐resolution full‐waveform velocity models with seismic reflection images to map the peak ring and impactite stratigraphy at the Chicxulub structure. International Ocean Discovery Program/International Continental scientific Drilling Program Site M0077 provides ground truth for our interpretations. The peak ring is narrower (∼10 km width) where it is high relief (600–700 m below seafloor) and wider (∼15 km width) where it is lower relief (1, 000–1, 200 m below seafloor). Both target asymmetry and angle of impact could have contributed to observed differences in peak ring morphology. We interpret a layer of lowered velocities as a resurge layer formed from the ocean resurge, seiche, and returning tsunami flowing into the newly formed impact basin. This graded suevite layer has an average thickness of 187 ± 58 m with only local thickness differences within the annular trough, peak ring, and central basin. These observations suggest that the returning ocean was of substantial height and energetic enough to carry debris across the entire topographic peak ring. We map impact melt rock throughout the crater, with a thick impact melt sheet in the central basin (>500 m), thin intermittent melt rock capping the peak ring, and a ∼500‐m thick layer of melt rock in the annular trough near the peak ring that thins toward the crater rim. We estimate that ∼70%–75% of the melt rock volume is in the central basin. We image features above and adjacent to the central basin melt sheet that we interpret as upflow zones associated with a long‐lasting hydrothermal system. Plain Language Summary: The Chicxulub structure formed ∼66 Ma by an impact event. We map features at the crater that provide new constraints on processes associated with the impact. The peak ring is a circular region of elevated topography within the crater that forms from the interaction between the downward and outward collapse of the central uplift and inward and downward collapse of the crater rim. We find that peak ring shape and depth is related to impact angle and differences in water depth at the impact site. We map a layer of rock fragments that formed as a result of water flowing into the newly formed impact basin; the properties of this layer indicate that the returning ocean was of substantial height and energetic. The energy of the impact was high enough to melt ∼10, 000 km 3 of rock at the impact site, most of which forms a melt sheet in the central basin. A hydrothermal system formed after the impact and formed upflow zones near the melt sheet. Key Points: Mapping of the resurge layer suggests that the returning ocean was energetic enough to carry debris across the elevated peak ring We estimate a melt rock volume of 9, 360–14, 500 km 3 with 70%–75% located within the central basin and 25%–30% in the annular trough We image features that we interpret as upflow zones above and near the melt sheet associated with a long‐lasting hydrothermal system